Climate Security Policy Coherence and Awareness Analysis Report: East Africa and Kenya - Scartozzi, Cesare M.; Savelli, Adam; Madurga Lopez, Ignacio M.; Schapendonk, Frans; Sarzana, Carolina; Pacillo, Grazia; Läderach, Peter R.D. (CGIAR System Organization, 2022)
This report summarises a climate security policy coherence and awareness assessment of policy and strategy documents extracted from climate-and peace and security-related sectors produced at the national level in Kenya. It makes use of a policy assessment framework developed specifically for the purpose of assessing coherence and climate security-sensitivity.